PENGARUH ESKTRAKURIKULER TARI TERHADAP KARAKTER DISIPLIN SISWA SMA NEGERI 1 UJUNG BATU - Nila Yusniati; Gimin Gimin; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of this research is a phenomenon which appears based on the pre-survey conducted by the researcher showed that there were many students are still lack of discipline in obeying the rules. One of the extracurricular that could improve students’ potential, interests and talents is dancing. The effect of dancing on discipline character is through children dance to energize their power in doing particular moves in specific music tempo as well as the the space that has been arranged. It means, students are taught to be discipline in the term of doing dancing moves which match with the moves pattern. Hopefully, training discipline moves could have any impacts to students and becoming their discipline character permanently. The aim of this research is to know the Effect of Dancing Extracurricular on Discipline Characters of SMA Negeri 1 Ujung Batu Students. The population of this research is SMA Negeri 1 Ujung Batu Students who joined dancing extracurricular with total of the sample is 25 students. The instrument of this research is observation, questionnaire, interview and documentation. In managing the data, researcher used quantitative descriptive. So the hypothesis in this study is accepted, where the dancing extracurricular and the effect on Discipline Characters of SMA Negeri 1 Ujung Batu Students showed a good result. So the hypothesis in this study is accepted, where the extracurricular dance and its influence on the disciplinary character of SMA Negeri 1 Ujung Batu students show very good results. Because based on the results of the calculations, it is known that the coefficient of determination (R square) is 0.768, which implies that the effect of the independent variable (dance extracurricular) on the dependent variable (discipline character) is 87.6%. Key Words: Dance Extracurricular, Effect And Character Of Discipline